Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.ymthe.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Gene Editing of Cystic Fibrosis Patient-Derived Airway Basal Cells Results in Functional CFTR Correction

Abstract: There is a strong rationale to consider future cell therapeutic approaches for cystic fibrosis (CF) in which autologous proximal airway basal stem cells, corrected for CFTR mutations, are transplanted into the patient's lungs. We assessed the possibility of editing the CFTR locus in these cells using zinc-finger nucleases and have pursued two approaches. The first, mutation-specific correction, is a footprint-free method replacing the CFTR mutation with corrected sequences. We have applied this approach for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 49 publications
1
59
0
Order By: Relevance
“…The successful restoration of CFTR might be enabled by the fact that all of the exons and introns downstream of exon 1 are left intact when cells are corrected using the Universal strategy. This result is also consistent with another study which showed that the insertion of a partial CFTR cDNA construct into intron 8 did not disrupt the open chromatin profile of the CFTR locus 43 . Future studies characterizing the open chromatin profile of corrected UABCs and HBECs will further inform us about the influence of our Universal strategy on the regulation of both CFTR and neighboring genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The successful restoration of CFTR might be enabled by the fact that all of the exons and introns downstream of exon 1 are left intact when cells are corrected using the Universal strategy. This result is also consistent with another study which showed that the insertion of a partial CFTR cDNA construct into intron 8 did not disrupt the open chromatin profile of the CFTR locus 43 . Future studies characterizing the open chromatin profile of corrected UABCs and HBECs will further inform us about the influence of our Universal strategy on the regulation of both CFTR and neighboring genes.…”
Section: Discussionsupporting
confidence: 92%
“…However, it was unknown if the addition of the full-length CFTR cDNA in the endogenous locus under the control of the native promoter would be sufficient to restore CFTR function. Since the CFTR cDNA with the appropriate homology arms cannot be packaged into one AAV capsid, insertion of partial CFTR cDNAs into introns 7 and 8 of the CFTR gene has been attempted and this approach that can potentially be used to treat ∼89% of CF patients 43 . This approach which did not enrich for corrected cells was tested in four CF patient samples and resulted in CFTR function that was 30-50% relative to non-CF controls.…”
Section: Discussionmentioning
confidence: 99%
“…Crane and colleagues showed that CFTR -corrected iPSCs, following induced differentiation in vitro, expressed functional CFTR protein ( Crane et al, 2015 ). A similar study used ZFNs to correct Phe508del and demonstrated restored CFTR protein expression and function in air-liquid interface cultures established from the edited basal cells ( Suzuki et al, 2020 ). TALEN technologies have also been used to restore normal CFTR expression and activity in organoids derived from Phe508del patient-derived iPSCs ( Fleischer et al, 2020 ).…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…Extending the use of Cftr KO animal models to correct the endogenous CFTR locus by gene editing is rather limited in that sense that most gene editing strategies are designed to correct a human disease-causing mutation. The KO models thus can only be of value for gene editing strategies aiming to integrate a super-exon ( Bednarski et al, 2016 ; Suzuki et al, 2020 ) in the Cftr locus (also see the section Correcting Multiple Mutations at Once ), that in case of a therapeutic super-exon encompasses all the necessary exons to correct the specific Cftr KO present in the animal model ( Wilke et al, 2011 ; McCarron et al, 2018 ; Rosen et al, 2018 ; Semaniakou et al, 2018 ).…”
Section: Cell and Animal Models Of Diseasementioning
confidence: 99%